Delitve in združitve poslovnih deležev v družbah z omejeno odgovornostjo - Čarni, Martin (Podjetje in delo, 2024)
The article examines divisions and mergers of business shares in private limited companies, mainly from the viewpoint point of their permissibility and the conditions under which divisions and mergers of business shares are permitted. The article exa-mines the aforementioned issues by initially presenting the relevant provisions of the applicable regulations in this area. The article then examines the possibility and conditions for the validity of divisions of business shares and presents the consequences of not meeting the conditions for the validity of divisions of business shares, together with the options for mitigation of irregularities with respect to divisions of business shares. In the final part, the article also discusses the permissibility of mergers of business shares in the applicable regulations and case law, as well as criticisms related, in particular, to the positions of the case law in this regard.
Keywords: annulment of entry in the court register; business share; court register; delisting; division of a business share; družba z omejeno odgovornostjo; merger of business shares; ničnost vpisa v sodni register; pogodba o prodaji poslovnega deleža; poslovni delež; private limited company; share purchase agreement; share transfer agreement; sodni register; združitev poslovnih deležev